Those Virtual People all Look the Same to me: Computer-Rendered Faces Elicit a Higher False Alarm Rate Than Real Human Faces in a Recognition Memory Task - Kätsyri, Jari (Frontiers in Psychology, 2018)
Virtual as compared with real human characters can elicit a sense of uneasiness in human observers, characterized by lack of familiarity and even feelings of eeriness (the “uncanny valley” hypothesis). Here we test the possibility that this alleged lack of familiarity is literal in the sense that people have lesser perceptual expertise in processing virtual as compared with real human faces. Sixty-four participants took part in a recognition memory study in which they first learned a set of faces and were then asked to recognize them in a testing session. We used real and virtual (computer-rendered) versions of the same faces, presented in either upright or inverted orientation. Real and virtual faces were matched for low-level visual features such as global luminosity and spatial frequency contents. Our results demonstrated a higher response bias towards responding “seen before” for virtual as compared with real faces, which was further explained by a higher false alarm rate for the former. This finding resembles a similar effect for recognizing human faces from other than one’s own ethnic groups (the “other race effect”). Virtual faces received clearly higher subjective eeriness ratings than real faces. Our results did not provide evidence of poorer overall recognition memory or lesser inversion effect for virtual faces, however. The higher false alarm rate finding supports the notion that lesser perceptual expertise may contribute to the lack of subjective familiarity with virtual faces. We discuss alternative interpretations and provide suggestions for future research.